Relationship Between Physiological Characteristics And Grain Yield of Barley (Hordeum Vulgare L.) Cultivars - Karaman, Mehmet (Bangladesh Journal of Botany, 2022)
The present study was carried out to determine the relationship between physiological characteristics with grain yield (GY) in barley cultivars. In this study, significant differences were found between varieties (p ≤ 0.01 or p ≤ 0.05) in all the characteristics, except GS77 (late milk formation) period Normalized Difference Vegetation Index (NDVI). While Erciyes, Çatalhüyük, Asutay and Aydanhanım barley cultivars were high yielding, and Bozlak was determined to be both high yielding and the most stable barley variety. In the correlation analysis, a positive and significant relationship was found between GY and NDVI in the GS83 (early dough formation) (r = 0.298*) and GS85 (dough formation) (r = 0.366**) periods. The GGE (genotype, genotype × environment) biplot model, visually presented the negative correlation between canopy temperature (CT) and GY. It was concluded that the selection of genotypes with high biomass, high flag leaf chlorophyll content, low canopy temperature and stable at the same time is important. Bangladesh J. Bot. 51(4): 737-745, 2022 (December)